Persuasion in the political marketplace: How firms snitch on rivals to encourage regulatory enforcement - Barber, Benjamin; Giustiziero, Gianluigi; Weschle, Simon (Strategic Management Journal, 2026)
Abstract Research Summary We study an important, but largely overlooked, non‐market strategy used by firms in the enforcement stage of policy: “snitching,” that is, providing intelligence about potential violations of their rivals in an attempt to persuade regulators to fine them. Building on political marketplace theory, we develop and test a theoretical model of how firms use snitching during regulatory enforcement. We show that in equilibrium, firms snitch when the rival's violations are likely to cause significant harm to the population. We then derive several boundary conditions outlining when firms will engage in more or less snitching. We find support for our theory in panel data on enforcement actions by the U.S. Environmental Protection Agency for more than 8000 facilities over 12 years. Managerial Summary Firms can use their corporate political activity (CPA) not only to help themselves, but also to snitch on their rivals. Using a formal model, we look at how CPA influences regulatory enforcement. We find firms are most likely to snitch on their rivals when their rivals' potential violations are likely to cause significant harm, since this is when regulators care the most. Our model also outlines when this is most and least likely to occur. We then test our theory using data from the U.S. Environmental Protection Agency (EPA) and find support for our claims. The EPA is more likely to fine facilities for infractions that process many toxic chemicals, but this effect is much greater when a firm's rivals are actively lobbying the EPA.